1354. Reducing vancomycin utilization rate in a level 4 NICU. (31st December 2020) - Chang, Millie R; Mongkolrattanothai, Kanokporn; Chin, Steven; Li, Yijie; Orbach, Regina; Stach, Leslie; Nair, Srikumar; Milisavljevic, Vladana
Abstract: Background: Vancomycin is frequently used empirically in suspected sepsis in neonatal intensive care unit (NICU). However, inappropriate or unnecessary use can lead to additional morbidities and emergence of drug resistant pathogens. Standardization of vancomycin use is imperative for safer and more efficient patient care. Methods: This study was part of a QI initiative to optimize vancomycin use by revising a standardized late onset sepsis (LOS) guideline with defined indications and criteria for empiric vancomycin. The implementation was started in 9/19 after completion of providers' education. To reduce seasonal variations, 1/19-3/19 (pre-guideline) and 12/19-2/20 (post-implementation) data was retrospectively compared, including demographics, antibiotic indications, days of therapy/1000 patient days (AUR), positive cultures, isolated pathogens and resistance profiles. Clinical outcomes and adherence to the guideline were evaluated. Wilcoxon rank sum test was applied for continuous variables and Pearson chi-square test was applied for categorical variables. p< 0.05 was considered significant. Results: There were 53 LOS antibiotic courses in 35 patients pre-guideline and 113 in 64 patients post-implementation. We found an overall increase in vancomycin AUR in the post-implementation period (66.92 vs. 70.72, respectively, p=0.79), however, largely due to appropriate use of vancomycin for documented infections with gram-positive pathogens (including CONS and MRSE). Mortality was not statistically significant between two periods (Table 1 and 2). Vancomycin was ordered significantly less empirically, as per guideline, in the post implementation period (71.43% vs 46.15%, p=0.02). Adherence to the LOS antibiotics guideline was 69%. Table 1: Demographic characteristics of infants pre and post-guideline Table 2: Therapy indication, medication exposure and clinical outcomes 30 days after LOS treatment pre and post-guideline Conclusion: Development of a standardized guideline for empiric antibiotic therapy is important to reduce unnecessary and inappropriate use of vancomycin. We demonstrated that use of a guideline significantly decreased vancomycin ordering as an empiric antibiotic. Further analysis is needed in order to identify safety of the guideline's criteria, factors contributing to unnecessary vancomycin use, as well as educational needs to ensure appropriate antibiotic use. Disclosures: All Authors : No reported disclosures